2008
DOI: 10.1029/2008ja013357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetospheric activity on the current sheet energy resonance ion distribution function signature

Abstract: [1] In this paper, we discuss the effects of magnetospheric activity (as measured by Kp) on an ion distribution function signature of nonlinear particle dynamics in current sheet-like magnetic fields. The signature manifests itself as a series of peaks in the ion distribution function whose separation depends on the fourth root of the energy and parameters that describe the current sheet structure. We have found that the signature is evident in Geotail CPI data for Kp 3+ and that the larger the value of Kp, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It is natural to expect that the properties of E z vary along the geomagnetic tail; that implies a nonuniform shifting of resonant regions and subsequent steepening (or flattening) of the beamlet scaling. This effect also brings some uncertainty in the estimation of current sheet parameters made on the basis of nonadiabatic acceleration without the normal component of electric field, as it was done by Holland et al [2008].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is natural to expect that the properties of E z vary along the geomagnetic tail; that implies a nonuniform shifting of resonant regions and subsequent steepening (or flattening) of the beamlet scaling. This effect also brings some uncertainty in the estimation of current sheet parameters made on the basis of nonadiabatic acceleration without the normal component of electric field, as it was done by Holland et al [2008].…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion was experimentally verified by Chen et al [1990b] in quiet time central plasma sheet distribution functions obtained aboard ISEE‐1. Later, having used Geotail CPI data, Holland et al [2008] investigated effects of magnetospheric activity (as measured by Kp) on an ion distribution function signature of nonlinear particle dynamics in current sheet. Holland et al [2008] have used the energy resonance signature for certain values of Kp in conjunction with measurements of the magnetic field to determine a lower bound on the current sheet thickness and have found that this lower bound decreases for increasing levels of magnetospheric activity.…”
Section: Introductionmentioning
confidence: 99%
“…If we launched particles from Northern and Southern Hemisphere simultaneously, this effect eventually leads to the overlapping of even and odd resonant regions (Figures b–c). This might be important in the light of the idea of using beamlets for remote sensing of the distant magnetotail [ Holland et al , ; Kovrazhkin et al , ].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Numerical fits to the data show that the symmetric surface of sections have energies given by 1/4 = N + 0.6 where N is a integer. It is this variation in the symmetry properties of the surface of section and the resulting partitioning of the particles into transient and chaotic orbits that lead to the distribution function signatures that have been observed in satellite data [ Chen et al , 1990a; Holland et al , 1999, 2006, 2008]. In Figure 3, we plot the value of β c as a function of 1/4 .…”
Section: Introductionmentioning
confidence: 89%